Between sociolinguistics and sociology of language -Definitions and concepts- - Fatima khelef (Social Empowerment Journal, 2020)
This research paper aims to shed light on an important knowledge field, concerned with the study of language in its relationship with society, by linking the linguistic lesson to the social framework, meaning the study of language and the influence of society in all its aspects in it. That is the result of the openness of linguistics to sociology, which produced a knowledge field known as sociolinguistics, and in this study, a separation will be made between the social linguistics and the sociology of language, in terms of concepts, definitions, and issues that each science addresses.